2007
DOI: 10.1364/josaa.24.003150
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-ratio error compensation for triangular-pattern phase-shifting profilometry

Abstract: We present an intensity-ratio error-compensation method to decrease the measurement error caused by projector gamma nonlinearity and image defocus in triangular-pattern phase-shifting profilometry. The intensity-ratio measurement error is first determined by simulating the measurement with the triangular-pattern phase-shifting method with ideal and real captured triangular-pattern images based on the ideal and real gamma nonlinearity functions. A lookup table that stores the intensity-ratio measurement error c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Since the proposed technique is based on the projection of binary patterns instead of gray levels intensities, it is possible to expand the operating tolerance to ambient light and avoid camera sensor saturation. We also show that is not necessary the use of phase unwrapping, as proposed in [6][7][8][9][10][11][12] for recovering the unwrapped intensity-ratio map. Finally, we have demonstrated that the periodic measurement errors due to gamma nonlinearity and defocus of the projector and camera are eliminated with the proposed method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the proposed technique is based on the projection of binary patterns instead of gray levels intensities, it is possible to expand the operating tolerance to ambient light and avoid camera sensor saturation. We also show that is not necessary the use of phase unwrapping, as proposed in [6][7][8][9][10][11][12] for recovering the unwrapped intensity-ratio map. Finally, we have demonstrated that the periodic measurement errors due to gamma nonlinearity and defocus of the projector and camera are eliminated with the proposed method.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative procedure to the projection of sinusoidal fringes consists in projecting two consecutive patterns on the test surface; a constant illumination pattern and a linear gray-level pattern (along the x axis) or equivalently, a triangular pattern onto the object [5][6][7][8][9][10][11][12]. Then, the 3-D profile is calculated as a simple intensity ratio between the two patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For phaseshifting multi-pattern SL methods, intensity variation information is coded in multiple patterns with phase shifts. Such intensity variations can be in the form of sinusoidal [7], [8], [9], [10], [11], [12], binary [13], [14], triangular [15], [16], hybrid [17], [18], or other shapes. Phase-shifting SL is the most representative method of SL because of its robustness and efficiency, and the sinusoidal pattern has the desirable properties of continuity and periodicity, and these properties make the sinusoidal pattern the most popular pattern for SL 3D imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The phase was then, optimized by an iterative algorithm. To compensate phase error for triangular phase shifting profilometry, an intensity ratio error compensation method [182] was proposed to reduce the measurement error belonging to gamma non-linearity and image defocus. It uses a minimum of two triangular patterns to measure the 3D surface and hence, a simple intensity ratio method was used.…”
Section: Passive Methods Of Error Compensationmentioning
confidence: 99%